2017
DOI: 10.1098/rspb.2017.1174
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of evolutionary digit reduction in fossil horses (Equidae)

Abstract: Digit reduction is a major trend that characterizes horse evolution, but its causes and consequences have rarely been quantitatively tested. Using beam analysis on fossilized centre metapodials, we tested how locomotor bone stresses changed with digit reduction and increasing body size across the horse lineage. Internal bone geometry was captured from 13 fossil horse genera that covered the breadth of the equid phylogeny and the spectrum of digit reduction and body sizes, from to To account for the load-bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
1
29
0
1
Order By: Relevance
“…Potential morphological adaptations for this mode of life comprise modifications of the locomotory and digestive systems. Possible locomotor adaptations to living in open habitats include the elongation of distal autopodial bones as well as the development of monodactyly and the reduction or loss of metapodials II and IV (Simpson, 1951;Shotwell, 1961;Janis and Wilhelm, 1993); however, we note that alternative explanations for digit reduction have been proposed (Thomason, 1986;Biewener, 1998;McHorse et al, 2017). The enhanced development of the stay-apparatus, which allows the individual to conserve energy while standing, is also potentially an adaptation to living in open habitats MacFadden, 1992, 1996).…”
Section: Uniqueness Of Adaptive Zonementioning
confidence: 88%
“…Potential morphological adaptations for this mode of life comprise modifications of the locomotory and digestive systems. Possible locomotor adaptations to living in open habitats include the elongation of distal autopodial bones as well as the development of monodactyly and the reduction or loss of metapodials II and IV (Simpson, 1951;Shotwell, 1961;Janis and Wilhelm, 1993); however, we note that alternative explanations for digit reduction have been proposed (Thomason, 1986;Biewener, 1998;McHorse et al, 2017). The enhanced development of the stay-apparatus, which allows the individual to conserve energy while standing, is also potentially an adaptation to living in open habitats MacFadden, 1992, 1996).…”
Section: Uniqueness Of Adaptive Zonementioning
confidence: 88%
“…Consistent with our findings, a 1975 anatomic text describes the 2nd and 4th Metacarpals in the Domesticate horse as variable, but generally equal in length, and located between two-thirds to three-quarters along the length of MC3 [ 21 ]. These references to the length of splint bones still exist for the Domesticate horse in scientific literature with the further adage that they are vestigial [ 23 , 24 ]. In contrast to this, the Dutch Konik horses examined in this study showed large variation in length between the 2nd and 4th Metacarpals, with the 2nd always longer than the 4th.…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that for the modern Domesticate horse, a reduction of the medial and lateral polydactyl digits to "Splint bones" together with the elongation of MC3 and MT3 for speed outweighed the demand for stabilisation or loadbearing [23]. This decreased the energetic cost of locomotion by lessening distal limb mass [23]. By comparison, it seems that increased stabilization and/or loadbearing was of greater evolutionary advantage to the ancestors of the Dutch Konik.…”
Section: Discussionmentioning
confidence: 99%